Electrospinning Hetero‐Nanofibers of Fe3C‐Mo2C/Nitrogen‐Doped‐Carbon as Efficient Electrocatalysts for Hydrogen Evolution. Issue 12 (20th April 2017) - Lin, Huanlei; Zhang, Wenbiao; Shi, Zhangping; Che, Minwei; Yu, Xiang; Tang, Yi; Gao, Qingsheng
Abstract: Heterostructured electrocatalysts with multiple active components are expected to synchronously address the two elementary steps in the hydrogen evolution reaction (HER), which require varied hydrogen‐binding strength on the catalyst surface. Herein, electrospinning followed by a pyrolysis is introduced to design Fe3 C‐Mo2 C/nitrogen‐doped carbon (Fe3 C‐Mo2 C/NC) hetero‐nanofibers (HNFs) with tunable composition, leading to abundant Fe3 C‐Mo2 C hetero‐interfaces for synergy in electrocatalysis. Owing to the strong hydrogen binding on Mo2 C and the relatively weak one on Fe3 C, the hetero‐interfaces of Fe3 C‐Mo2 C remarkably promote HER kinetics and intrinsic activity. Additionally, the loose and porous N‐doped carbon matrix, as a result of Fe‐catalyzed carbonization, ensures the fast transport of electrolytes and electrons, thus minimizing diffusion limitation. As expected, the optimized Fe3 C‐Mo2 C/NC HNFs afforded a low overpotential of 116 mV at a current density of −10 mA cm −2 and striking kinetics metrics (onset overpotential: 42 mV, Tafel slope: 43 mV dec −1 ) in 0.5 m H2 SO4, outperforming most recently reported noble‐metal‐free electrocatalysts. Abstract : Hetero‐nanofibers of Fe3 C‐Mo2 C/N‐doped carbon with tunable composition are fabricated by electrospinning followed by pyrolysis, resulting in synergic enhancement to catalyze the two elementary steps in the hydrogen evolution reaction. The optimized nanofibers present high activity and good stability in acidic electrolytes, performing among the best current noble‐metal‐free electrocatalysts.